Catalytic fast pyrolysis of pressure-sensitive adhesives wastes using Py-GC/MS. Issue 6 (19th March 2018) - Helong, Hui; Wang, Ze; Lu, He; Songgeng, Li
ABSTRACT: Catalytic fast pyrolysis of pressure-sensitive adhesives (PSAs) wastes was tested by Py-GC/MS for potential preparation of fuels from PSAs wastes. The effects of ZSM-5 and the ash from the combustion of PSAs on the compositions of the condensable and incondensable products were investigated. It was found that the oxygen content in the condensable product is reduced with more generated aromatics over ZSM-5. Ash presented positive effects on the upgrading of incondensable products with a favorable H2 /CO ratio of 2 and a higher caloric value. Reaction routes of chain aliphaticcompounds under the catalysis of ZSM-5 and ash were respectively proposed.